(untitled) (EU and comparative law issues and challenges series (ECLIC), 2023)
The paper tackles the conflicts of laws on property rights over cryptocurrencies, starting from characterization issues. Building upon the distinctive nature of cryptocurrencies as “pure” de facto assets, that do not give a claim against an issuer, and the relevance of control over said assets as a suitable alternative to the traditional possession, the paper supports the characterization in terms of “assets”, over which property rights may, subject to the relevant lex causae, be constituted and enjoyed. By examining the available options for a conflict-of-law regime and considering the first legislative efforts conducted in this area of law both at the supranational and national level, the elective situs approach is identified as the most appropriate, possibly backed by some regulatory requirement, whilst different approaches are envisaged for the fall-back rule applicable to cryptocurrencies originated in, respectively, permissioned and permissionless DLT systems.